2019
DOI: 10.1111/dgd.12639
|View full text |Cite
|
Sign up to set email alerts
|

Maternal almondex, a neurogenic gene, is required for proper subcellular Notch distribution in early Drosophila embryogenesis

Abstract: Notch signaling plays crucial roles in the control of cell fate and physiology through local cell–cell interactions. The core processes of Notch signal transduction are well established, but the mechanisms that fine‐tune the pathway in various developmental and post‐developmental contexts are less clear. Drosophila almondex, which encodes an evolutionarily conserved double‐pass transmembrane protein, was identified in the 1970s as a maternal‐effect gene that regulates Notch signaling in certain contexts, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 66 publications
(138 reference statements)
1
9
0
Order By: Relevance
“…We first showed that the knockout allele of amx ( Drosophila homolog of TM2D3 ) generated by CRISPR is phenotypically indistingusiable from the classic amx 1 allele and displays female sterility and a maternal-effect neurogenic defect. Recently, we reported that this allele also shows a maternal-effect inductive signaling defect to specify the mesoectoderm during embryogenesis which is another Notch-dependent event [ 59 ], demonstrating that amx is maternally required for multiple Notch signaling dependent processes during embryogenesis. In addition, we generated the first knockout alleles of amrt ( Drosophila ortholog of TM2D2 ) and bisc ( Drosophila ortholog of TM2D1 ) and documented that each null allele phenotypically mimics the loss of amx .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first showed that the knockout allele of amx ( Drosophila homolog of TM2D3 ) generated by CRISPR is phenotypically indistingusiable from the classic amx 1 allele and displays female sterility and a maternal-effect neurogenic defect. Recently, we reported that this allele also shows a maternal-effect inductive signaling defect to specify the mesoectoderm during embryogenesis which is another Notch-dependent event [ 59 ], demonstrating that amx is maternally required for multiple Notch signaling dependent processes during embryogenesis. In addition, we generated the first knockout alleles of amrt ( Drosophila ortholog of TM2D2 ) and bisc ( Drosophila ortholog of TM2D1 ) and documented that each null allele phenotypically mimics the loss of amx .…”
Section: Discussionmentioning
confidence: 99%
“…By tagging the amx genomic rescue construct with a 3xHA tag that does not influence the function of Amx, we observed that 3xHA::Amx is localized to the plasma membrane as well as intracellular puncta, which likely reflects intracellular vesicles. Interestingly in embryos laid by amx Δ mutant females, we observed a mild and transient but significant alteration in Notch distribution during early embryogenesis [ 59 ]. Moreover, we observed a strong accumulation of Notch when we overexpressed Amx ΔECD in the developing wing primordium.…”
Section: Discussionmentioning
confidence: 99%
“…By tagging the amx genomic rescue construct with a 3xHA tag that does not influence the function of Amx, we observed that 3xHA::Amx is localized to the plasma membrane as well as intracellular puncta, which likely reflects intracellular vesicles. Interestingly in embryos laid by amx D mutant females, we observed a mild and transient but significant alteration in Notch distribution during early embryogenesis (Das et al, 2020). Moreover, we observed a strong accumulation of Notch when we overexpressed Amx DECD in the developing wing primordium.…”
Section: Discussionmentioning
confidence: 65%
“…We first showed that the knockout allele of amx (Drosophila homolog of TM2D3) generated by CRISPR is phenotypically indistingusiable from the classic amx 1 allele and displays female sterility and a maternal-effect neurogenic defect. Recently, we reported that this allele also shows a maternal-effect inductive signaling defect to specify the mesoectoderm during embryogenesis, which is another Notch-dependent event (Das et al, 2020), demonstrating that amx is maternally required for multiple Notch signaling dependent processes during embryogenesis. In addition, we generated the first knockout alleles of amrt (Drosophila ortholog of TM2D2) and bisc (Drosophila ortholog of TM2D1) and documented that each null allele phenotypically mimics the loss of amx.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, a rare deleterious variant in the human gene TM2D3 was found to have a strong association with increased risk of late-onset AD [ 182 ]. Studies in Drosophila have shown that the mutants of the TM2D3 ortholog, almondex ( amx ), show strong maternal-effect Notch LOF phenotypes [ 209 , 210 ]. In addition, epistasis experiments have suggested that amx likely regulates the function of γ-secretase [ 211 ].…”
Section: Notch Signaling As a Modifier Of Neurodegenerative Diseasmentioning
confidence: 99%